Implementasi Manajemen Evaluasi Pembelajaran Terpadu untuk Pendidikan Islam Anak Usia Dini (PIAUD) - Manora, Hecksa; Khasanah, Nevi Laila; Ertati, Ertati (STAI Bumi Silampari, 2023)
Islamic early childhood education (PIAUD) helps children develop character and religious awareness. Effective learning in PIAUD must be evaluated to ensure its success. PIAUD still struggles with holistic and integrated learning evaluation. The research focuses on model creation and implementation testing of integrated learning evaluation management in PIAUD. Researchers, educators, other PIAUD stakeholders collaborate on qualitative action research. The research shows that integrated learning evaluation management improves PIAUD learning evaluation understanding and practice. Teaching methods, resources, and child development can be assessed using this paradigm. Additionally, parents participate in the evaluation procedure, which strengthens the PIAUD-family partnership. This study found that integrated learning assessment management improves early childhood Islamic education. Implementing PIAUD educator guidelines and raising parents' understanding of their participation in children's learning are practical implications.